Adjustable conduits for guided peripheral nerve regeneration prepared from bi-zonal unidirectional and multidirectional laminar scaffold of type I collagen (2021)
Shortness of donor nerves has led to the development of nerve conduits that connect sectioned peripheral nerve stumps and help to prevent the formation of neuromas. Often, the standard diameters of these devices cannot be adapted at the time of surgery to the diameter of the nerve injured. In this work, scaffolds were developed to form filled nerve conduits with an inner matrix with unidirectional channels covered by a multidirectional pore zone. Collagen type I dispersions (5 mg/g and 8 mg/g) were sequentially frozen using different methods to obtain six laminar scaffolds (P1 to P5) formed by a unidirectional (U) pore/channel zone adjacent to a multidirectional (M) pore zone. The physicochemical and microstructural properties of the scaffolds were determined and compared, as well as their biodegradability, residual glutaraldehyde and cytocompatibility. Also, the Young's modulus of the conduits made by rolling up the bizonal scaffolds from the unidirectional to the multidirectional zone was determined. Based on these comparisons, the proliferation and differentiation of hASC were assessed only in the P3 scaffolds. The cells adhered, aligned in the same direction as the unidirectional porous fibers, proliferated, and differentiated into Schwann-like cells. Adjustable conduits made with the P3 scaffold were implanted in rats 10 mm sciatic nerve lesions to compare their performance with that of autologous sciatic nerve grafted lesions. The in vivo results demonstrated that the tested conduit can be adapted to the diameter of the nerve stumps to guide their growth and promote their regeneration.